Two decades of research on strategic alliances: analysis of citations, co-citations and themes researched - Ferreira, Manuel Portugal (2021)
Research on strategic alliances has a long tradition in management studies. Strategic alliances have been investigated using multiple theoretical lenses from RBV to agency and transaction cost, and diverse contexts, from the semiconductor to airline industries. In this study we scrutinize the extant strategic alliance research in thirty-one top-ranked business/management journals, over a twenty-year period, from 1993 to 2012. In a sample of 866 articles we conducted citation and co-citation analyses employing social network techniques and factor analysis to identify research themes and make sense of the stock of accumulated knowledge and theoretical trends. We were able to identify some shifts in research over time, namely from a focus on performance and theoretical emphasis on transaction cost theory and governance concerns, moving to a learning and knowledge transfer approach, social networks and collaboration. This study provides the foundations over which future research may develop to fill conceptual and empirical gaps.